Increased Trust in the Finnish UBI Experiment - Is the Secret Universalism or Less Bureaucracy? Basic Income Studies, - de Andrade Luis; Ylikännö Minna; Kangas Olli (Walter de Gruyter GmbH, 2022)
Bureaucratic selectivity mechanisms are the true colours of welfare states, stigmatising benefit recipients while hampering their trust in institutions and society at large. Universal policies such as the Universal Basic Income (UBI) could protect recipients’ trust by circumventing selectivity paraphernalia. By analysing regressions on the Finnish UBI experiment’s survey data, we assess the links from policy selectivity to trust in the benefit-providing institution and generalised trust through the pathway of reduced bureaucratic experience. More specifically, we analyse whether receipt of UBI leads to greater trust directly or while accompanied by an actual or perceived reduction in bureaucracy. According to our results, UBI is accompanied by greater trust, while selectivity does not necessarily lead to less trust or perception of less bureaucracy. However, in our analysis, policy selectivity did not directly correlate to recipients’ reported bureaucratic experiences, and their relationship with trust proved tricky: selectivity did not risk recipients’ trust in the policy-implementing institution, but generalised trust in other people was lowered. Thus, selective benefit recipients might be prone to self-inflicted stigma, hampering their trust in other people, regardless of actual bureaucratic experiences or trust in the welfare system.